A efetividade de uma assessoria de comunicação: estudo em um setor de uma universidade pública - Martins, João Cubas (2019)
The existence of sectors of organizational communication in public institutions is not a guarantee that it will process adequately or effectively, in view of the objectives for which they are created. In this sense, the dissertation seeks to identify the degree of effectiveness of communication vehicles in the Biological Sciences Sector (SCB) of the Federal University of Paraná. For this, the effectiveness of the activities of the Advisory to Educational Projects and Communication (ASPEC), responsible for the internal communication management of the Sector was studied. The methodology used has a qualitative approach, with interviews with those responsible for the SCB management, and quantitative, with a survey questionnaire with the users of the communication services. In the theoretical framework, presenters discuss the effectiveness of public services and communicative processes and communication advisory services. The study is compatible with the research line of Organizational Transformation and Innovation because it evaluates the changes that occurred in the Sector studied due to the creation of ASPEC consultancy. In the approach of public administration, this study analyzes the effectiveness from the point of view of the verification of the communication activities in the SCB, in order to verify if they are related to the objectives predicted in its creation. It was verified that the effectiveness occurs in parts, although there is recognition of the communication activities, the public suggests the improvement of some approaches, relative to the content and the contact with the community.